Cloud Security Threats and Issues-A Review - Sood, R; Sharma, R (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is one of the best on-demand network access service available to a large shared pool of computing resources in today’s world. There are various economic benefits of cloud computing which are widely recognized. Cloud computing help users to avail benefits of having large storage (IAAS), variety of OS (PAAS) and other softwares (SAAS) at their premises without the need to have them at their own hardware level. Apart from these economic benefits, public clouds still haven’t seen widespread adoption, especially by enterprises. Most large organizations today run private clouds, in the sense of virtualized and geographically distributed data centers, but rarely rely primarily on externally managed resources. Major reason behind this is the security concerns involved in existing cloud infrastructures which includes hardware failures, software bugs, power outrages, server miniconfiguration, malware and inside threats. The aim of this paper is to throw light on various Cloud security threats and issues as well as security issues inherent within the context of cloud computing and cloud infrastructure.